APPLICATION OF IPOM OEA BATATA STARCH MUCILAGE AS SUSPENDING AGENT IN OSELTAMIVIR SUSPENSION - R., Kusuma; A., Samba Shiva Rao (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of the study was to search for a cheap and effective natural raw material that can serve as an alternative suspending agent in the formulation of oseltamivir suspension. The phytochemical and the physicochemical properties of the mucilage of Ipomoea batata starch were studied. Methods: The suspending properties of mucilage extract of I. batata starch was evaluated comparatively with that of acacia, xanthum gum and sodium alginate using model formulations at concentrations of 0.75, 1.5and 3.5% w/v. The Prepared suspensions were evaluated by studying different parameters like pH, sedimentation volume, redispersibility, Flow rate (F), viscosity, degree of flocculation, effect, effect of temperature and stability studies. Results: The results showed the presence of flavonoids, saponin, protein, carbohydrate and reducing sugars. The rheological properties of suspension showed that As the concentration of suspending agent increased viscosity also get increased which reduces the sedimentation and contributes to the stability of suspension. Increase in viscosity avoids the particle aggregation so particles remain in a flocculated state. While an increase in temperature did not significantly increased the viscosity of suspension. The order of stability of suspension in terms of sedimentation profile ranked thus: OF3 (3%w/v IBSM)>OF12 (3%w/v SA)>OF6 (3%w/v AG)>OF9 (3%w/v XG)>B (5%w/v potato starch). Conclusion: These results indicate that mucilage from I. batata starch in oseltamivir suspension has low sedimentation rate, medium viscosity and easily dispersible and can therefore serve as suspending agent in formulations of suspensions of sparingly soluble drugs.